Design of Interference-Resilient Medium Access for High Throughput WLANs - Luca Reggiani; Andrea Gola; Gian Mario Maggio; Gianluigi Tiberi (International Journal of Distributed Sensor Networks)
The proliferation of wireless communications systems poses new challenges in terms of coexistence between heterogeneous devices operating within the same frequency bands. In fact, in case of high-density concentration of wireless devices, like indoor environments, the network performance is typically limited by the mutual interference among the devices themselves, such as for wireless local area networks (WLANs). In this paper, we analyze a protocol strategy for managing multiple access in wireless networks. A network of sensors colocated with the WLAN terminals forms a control layer for managing the medium access and scheduling resources in order to limit collisions and optimize the WLAN data traffic; this control layer is based on a low-power wideband technology characterized by interference robustness, like CDMA (code division multiple access) or UWB (ultra-wideband) for sensors. In this work, we perform an analytical and simulative performance study of the saturated throughput, showing numerical results for the UWB-IR (Impulse Radio) sensors case and highlighting the advantage that can be provided particularly in very high capacity systems, which constitute the necessary evolution of current WLAN versions.